Is Sharia Pawnshop being important for Indonesian society: Quadruple Helix Analysis - Aris Machmud; Yusup Hidayat; Rakhsan Ghifari (Faculty of Law, Universitas Pekalongan, 2023)
The development of sharia pawning is very rapid, viewed from the large number of branch offices opening due to the increasing transactions throughout Indonesia. The problem is the existence of Sharia pawning as driven by the socio-cultural conditions of society. The form of research used is normative juridical with a descriptive-analytical approach. The legal sources used are obtained from primary and secondary sources and use interdisciplinary studies in analyzing problems in Sharia pawning. This research aims to understand the existence of sharia pawning in Indonesia. In this research, the existence and position of Sharia pawn in improving lower middle-class society and MSMEs. The conclusions of this research show that the existence and position of Sharia pawning have shifted conventional pawning due to the increase in public trust in non-interest pawning and excellent service from these non-bank financial institutions in the eyes of the public, tiny and medium businesses. The use of four pillars - academics, business, government, and society - can further maximize the potential and increase the performance of this Sharia pawn in Indonesia.